Enhancing Sheep Rations: Optimal Ammoniated Palm Fronds Utilization with Lerak Fruit (Sapindus Rarak) and Probiotic Supplementation - Essy Laura; Mardiati Zain; Fauzia Agustin (Andalasian Livestock, 2024)
This study aimed to assess the impact of lerak fruit and probiotic supplementation on varying levels of ammoniated palm fronds in sheep rations, as well as to determine the optimal inclusion rate of ammoniated palm fronds in the presence of lerak fruit and probiotics. Employing an experimental approach, a Latin Square Design was utilized, with four sheep as rows, four periods as columns, and four rations as treatments. Treatments included: A) 50% field grass + concentrate, B) 20% field grass + 30% ammoniated palm fronds + 50% concentrate + lerak fruit + probiotics, C) 10% field grass + 40% ammoniated palm fronds + 50% concentrate + lerak fruit + probiotics, and D) 0% field grass + 50% ammoniated palm fronds + 50% concentrate + lerak fruit + probiotics. Results indicated significant differences (P<0.05) between dry and organic matter intake treatments and body weight gain. However, no significant differences (P>0.05) were observed in the digestibility of dry and organic matter. These findings suggest that supplementation with up to 40% ammoniated palm fronds in sheep rations, probiotics, and lerak fruit yielded comparable digestibility and livestock performance as the control. This study provides valuable insights into optimizing sheep rations with alternative feed ingredients, contributing to enhanced animal nutrition practices.